Archaeological Prospection - Archaeological Prospection (Wiley, 2026)
Archaeological Prospection is a comprehensive and up-to-date guide of scientific techniques available for the study of the near-surface environment. Our interdisciplinary journal promotes international collaboration amongst practitioners and academics.
FI 1.08
Q2
Keywords: Earth; Space & Environmental Sciences; Earth Sciences; Ciencias de la Tierra; Acuerdos transformativos; Transformative agreements; Arqueología; Prospección arqueológica; Excavaciones arqueológicas